Effect of core hydrophobicity on the electrophoresis of pH-regulated soft particles - Bharti; Gopmandal, Partha P; Sinha, R. K; Ohshima, H (Soft matter, 2021)
We propose a theoretical study on the electrophoresis of core-shell composite soft particles considering the effect of hydrodynamic slip length of the hydrophobic inner core. The surface of the inner core as well as the soft polymeric shell bear zwitterionic functional groups and the charged conditions depend on the nearby micro-environment. Within a low potential and weak electric field framework, the mathematical equations of the generalized electrokinetic theory for soft surfaces are solved analytically subject to appropriate boundary conditions, and a general electrophoretic mobility expression in an integral form involving the pH-dependent electrostatic potential is derived. With the help of suitable numerical schemes, electrophoretic mobility can easily be obtained. The effect of hydrophobicity of the inner core on the electrophoretic mobility of pH-regulated soft particles is illustrated for a wide range of pertinent parameters. We propose a theoretical study on the electrophoresis of pH-regualted soft particles considering the effect of hydrodynamic slip length of the hydrophobic inner core.